Avelumab plus axitinib vs. sunitinib for advanced renal-cell carcinoma - Zhang, Yue; Wu, Shenhong (Translational Cancer Research; Vol 8, Supplement 6 (December 20, 2019): Translational Cancer Research, 2019)
Treatment for renal cell carcinoma (RCC) is undergoing landscape changes in recent years with introduction of immune check point inhibitors and combination regimens. Sunitinib and pazopanib are vascular endothelial growth factor receptor (VEGFR) tyrosine kinase inhibitors (TKIs). They have been the standard of care for the first line treatment of advanced RCC over a decade (1-3). Axitinib, sorafenib; the anti-VEGF monoclonal antibody bevacizumab; and the mammalian target of rapamycin (mTOR) inhibitors everolimus were often used in the second line or refractory setting with only 15–25% response rate, significant toxicities and limited time for progression free survival (PFS) and overall survival (OS) (4-6). Avelumab plus axitinib combination is just approved for first-line treatment of patients with advanced RCC on May 14, 2019. This breakthrough offers RCC patients with another new treatment option and better outcome based on the result from a phase III, randomized, multicenter, open-label JAVELIN Renal 101 trial (NCT02684006).